Multivariate Factor Analysis on The Influence Of Women's Leadership On MSME Business Success - Fahrizal Gema Akbar; Hardi Elfandi; Rian Setiawan; Osep Hijuzaman (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2026)
Women’s leadership has gained increasing attention as a strategic factor in enhancing business performance; however, comprehensive empirical evidence in Indonesia remains limited. This study aims to examine the influence of women’s leadership on business success in Indonesia using a multivariate approach. Specifically, it identifies the leadership styles that most strongly contribute to key business performance indicators, including revenue growth, operational efficiency, and business sustainability. In addition, this study investigates the mediating roles of innovation, decision-making quality, team communication, and employee motivation, as well as the moderating effects of access to capital, organizational culture, digital literacy, and business networks on the relationship between women’s leadership and business success. This research employs a quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS) based on data collected from women-led enterprises across various business sectors and firm sizes in Indonesia. The results indicate that women’s leadership has a significant direct effect on organizational performance, while its effect on business success is mainly indirect through innovation capability, effective decision-making, and strong team communication and motivation. Furthermore, access to capital, supportive organizational culture, and digital literacy strengthen the impact of women’s leadership on business outcomes, with variations observed across sectors and company sizes. The study concludes that the effectiveness of women’s leadership in driving business success is strongly shaped by organizational mechanisms and contextual business environments.